Health education and menstrual hygiene practices among junior secondary school students in Rivers West Senatorial District, Rivers State, Nigeria - Peter-Kio , Opirite Boma; Nduka, Christiana (Faculty of Natural and Applied Sciences Journal of Health, Sports Science and Recreation, 2024)
This study examined the effect of health education on menstrual hygiene practice among junior secondary school students in Rivers West Senatorial District. The pre-test and post-test design was adopted with a population comprising 21,929 female junior secondary school students in Rivers West Senatorial District. A sample size of 200 was selected using a multi-staged sampling procedure. The instrument for data collection was a structured test instrument titled “Test Instrument on Knowledge and Practice of Menstrual Hygiene (TIoPMeHy)”, with a reliability coefficient of 0.87. Data collected was analyzed with the aid of the Statistical Product for Service Solution (SPSS) version 23.0 using mean and analysis of covariance (ANCOVA). The study's finding showed that health education had a positive effect on personal hygiene management during menstruation with a mean difference of 1.52, and menstrual hygiene practice with a mean difference of 2.82. The finding of the study also revealed that health education had a significant effect on personal hygiene management during menstruation [F(1,99) = 1.59, p<0.05], and menstrual hygiene practice [F(1,99) = 5.97, p<0.05] among junior secondary school students. It was concluded that health education has the potential to influence the practice of health behaviour and also translate knowledge into the practice of menstrual hygiene among female secondary school students. It was recommended among others that, health agencies should collaborate with primary healthcare workers to ensure weekly or monthly visits to schools with the aim of monitoring and enforcing good menstrual hygiene among female students.